2023
DOI: 10.3390/ijms241210231
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mechanical/Chemical Properties and Cytotoxicity of Resin-Modified Glass Ionomer Cements Containing Sr/F-Bioactive Glass Nanoparticles and Methacrylate Functionalized Polyacids

Abstract: This study prepared low-toxicity, elemental-releasing resin-modified glass ionomer cements (RMGICs). The effect of 2-hydroxyethyl methacrylate (HEMA, 0 or 5 wt%) and Sr/F-bioactive glass nanoparticles (Sr/F-BGNPs, 5 or 10 wt%) on chemical/mechanical properties and cytotoxicity were examined. Commercial RMGIC (Vitrebond, VB) and calcium silicate cement (Theracal LC, TC) were used as comparisons. Adding HEMA and increasing Sr/F-BGNPs concentration decreased monomer conversion and enhanced elemental release but w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The results from the current study also correlated with the previous study, which indicated the good biocompatibility of conventional GICs to both L929 mouse fibroblasts and human dental pulp cells [ 67 ]. A satisfactory cytocompatibility was usually observed with conventional GICs compared with resin-modified GICs due mainly to the lack of toxic components such as 2-hydroxyethyl methacrylate [ 11 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results from the current study also correlated with the previous study, which indicated the good biocompatibility of conventional GICs to both L929 mouse fibroblasts and human dental pulp cells [ 67 ]. A satisfactory cytocompatibility was usually observed with conventional GICs compared with resin-modified GICs due mainly to the lack of toxic components such as 2-hydroxyethyl methacrylate [ 11 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, RMGIC has shown an increase in polymeric shrinkage, microleakage, low wear resistance and unstable colour. [22][23][24] Giomers show higher optical properties than RMGIC. 25 Giomers contain pre-reacted glass-ionomer fillers in the resin matrix.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the composites containing bioactive glass enhanced the precipitation of calcium phosphates to a demineralized dentin [ 15 ]. Furthermore, the release of ions or particles could inhibit the growth of pathogenic oral microorganisms without causing serious cytotoxic effects [ 16–18 ]. However, the addition of the bioactive glass at high concentration demonstrated the negative effects on the mechanical and physical properties of the materials [ 19 ].…”
Section: Introductionmentioning
confidence: 99%